KONSEP DAN IMPLEMENTASI TATA KELOLA PERUSAHAAN YANG BAIK PADA PERBANKAN SYARIAH DI INDONESIA - Sugeng Priyono (Ad-Deenar: Jurnal Ekonomi dan Bisnis Islam, 2019)
This study aims to examine the concepts and implementation of Good Corporate Governance (GCG) in Islamic banking in Indonesia. Corporate governance represents the principles of management that have actually existed in the history of human civilization and have been practiced since the first time there was a company. This research is a field research that is sharpened by literature. This research is descriptive in nature, seeks to examine GCG policies and find ideas for strengthening regulations in fulfilling sharia aspects and describing the implementation of GCG in Islamic banking in Indonesia. The method used in data analysis is a qualitative method, namely by presenting in the form of descriptions and concepts. The data obtained were analyzed by descriptive analysis techniques with deductive logic. The results of this research prove that the implementation of GCG on BMI has been implemented quite well, BSM is very good, and BNI Syariah is good. The management performance of Islamic banks, namely the implementation of GCG, consists of Transparency (Openness), Accountability, Responsibility, Professionalism, Independence, and Fairness, also committed with Sharia Compliance. GCG can form an Islamic work culture. Then a periodic and continuous assessment is carried out and strived to be carried out properly in accordance with regulations. The assessment shows that the implementation of GCG in BMI, BSM, and BNI Syariah is in accordance with the rules covering three aspects of governance; governance structure, governance process and governance outcome. The author's research focuses more on the concept and implementation of GCG in Islamic banking